Renal Cell Carcinoma Metastasis from Biopsy Associated Hematoma Disruption during Robotic Partial Nephrectomy - Christopher Caputo; Ziho Lee; Andrew Harbin; Daniel Eun (Case Reports in Urology)
We describe a case in which a patient with a past medical history of ovarian cancer received a diagnostic renal biopsy for an incidentally discovered renal mass. During left robotic partial nephrectomy (RPN), a perinephric hematoma was encountered. The hematoma was not present on preoperative imaging and was likely a result of the renal biopsy. The renal cell carcinoma (RCC) and the associated hematoma were widely excised with negative surgical margins. On follow-up imaging at five months postoperatively, a recurrent renal mass at the surgical resection bed and several new nodules in the omentum were detected. During completion left robotic total nephrectomy and omental excision, intraoperative frozen sections confirmed metastatic RCC. We believe that a hematoma seeded with RCC formed as a result of the renal biopsy, and subsequent disruption of the hematoma during RPN caused contamination of RCC into the surrounding structures.